From public to private: understanding the decline in government school enrolment in India (2012–2024) - Meena, Amrat Lal (Journal of Social Review and Development, 2025)
Over the past decade, India has witnessed a significant shift in school enrolment patterns, with a growing proportion of students transitioning from government to private schools. This paper investigates this enrolment shift across 20 major Indian states and all states and union territories combined, using quantitative data from Unified District Information System for Education (UDISE+), maintained by the Ministry of Education, Government of India, MOSPI, and the ASER 2024 report. The analysis identifies and explores key drivers of this trend, including economic indicators such as per capita State Domestic Product (SDP), the prevalence of English-medium instruction in government schools, school infrastructure quality, and comparative learning outcomes. Findings indicate a strong association between higher income levels, better learning outcomes in private schools, and increased enrolment in private institutions. Furthermore, states with a lower proportion of English-medium and well-facilitated government schools experienced sharper declines in government school enrolment. The paper concludes by discussing the implications of this shift for educational equity and public policy, emphasizing the need for systemic reforms to enhance the quality, accountability, and competitiveness of government schools in India.